ANALISIS PENERJEMAHAN KALIMAT ACAK BAHASA JEPANG KEDALAM BAHASA INDONESIA - Dance Wamafma (Janaru Saja Jurnal Program Studi Sastra Jepang, 2024)
AbstractRandom sentences are a phenomenon of Japanese structure based on the distribution of structural components. The S Scrambling sentence for example places the position of the verb phrase in front of the subject, M Scrambling randomizes the beginning position of the sentence to the final position and the L Scrambling model places certain components across the clause boundaries. These sentences became the object of the Japanese source language (Bsu) which was transferred into Indonesian. The purpose of this study is to describe the location and meaning of the filler of functions, categories, and roles of sentences translated into Indonesian target languages (Bsa). Through the descriptive method of analysis carried out on the translation results of a group of student respondents, it was found that there was an extreme randomization of sentence function filler components, in the structure of functions, categories, and roles with the Japanese Bsu scramblingsentences. The large gap between the results of the Bsa translation and the core of the Bsu sentence provides an important warning for the teachers of the honyaku course, so that the development of translation techniques and methods arranges teaching to find the right translation model. Keywords: random, scrambling, translation; source language (Bsu); Target language (BSA) AbstrakKalimat acak merupakan satu fenomena struktur bahasa Jepang berdasarkan distribusi komponen strukturnya. Kalimat S Scrambling misalnya menempatkan posisi frase verbanya di depan subjek, M Scrambling mengacak posisi awal kalimat menjadi posisi akhir dan model L Scrambling menempatkan komponen tertentu melintasi batasan klausa. Kalimat-kalimat ini menjadi objek bahasa sumber (Bsu) Jepang yang dialihkan ke dalam bahasa Indonesia. Tujuan penelitian ini untuk menggambarkan letak dan makna pengisi fungsi, kategori, dan peran kalimat hasil terjemahan bahasa sasaran (Bsa) Indonesia. Melalui metode deskriptif analisis yang dilakukan terhadap hasil terjemahan responden sekelompok mahasiswa, didapati adanya pengacakan komponen pengisi fungsi kalimat yang cukup ekstrim, pada struktur fungsi, kategori, dan peran dengan kalimat scrambiling Bsu Jepangnya. Begitu besarnya jarak hasil penerjemahan Bsa dengan inti kalimat Bsu tersebut memberikan peringatan penting bagi pengampu mata kuliah honyaku, agar pengembangkan teknik dan metode penerjemahan menata pengajaran untuk menemukan model penerjemahan yang tepat.Kata kunci: acak, srambling, penerjemahan; bahasa sumber (Bsu); bahasa sasaran (Bsa)